LEKSIKON PERIKANAN DI DANAU SENTARUM KABUPATEN KAPUAS HULU - Noviyanti, Anggi; Muzammil, Ahmad Rabi ul; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study provides a view of how the use of everyday language in relation to fisherman activities in Lake Sentarum in fisheries uses the dialect of Malay language Kapuas Hulu. The problem of this research is how is the form of lingual units, the meaning of fisheries lexicon, cultural meaning in the form of mythical speech, prohibited abstinence, oral literature, and its implementation in Indonesian language learning in schools. This research aims to describe based on existing problems. The theory used is semantic, ethnolinguistic, meaning and meaning. This study uses a qualitative approach to descriptive methods. Research subjects were native speakers of the Malay language Kapuas Hulu in Lake Sentarum Kapuas Hulu with research objects in the form of words and phrases. Data analysis is done by obtaining data, then the data is classified and described based on existing problems, then implemented in Indonesian language learning in schools. The results of the study of all lexicon data are 60 data based on tools, activities, and results. Cultural significance of 6 utterances based on myth, prohibited abstinence and oral literature. As well as supplementary teaching materials there are 2 texts, the procedure text, and the description text. Keyword: vocabulary, fisheries, Kapuas Hulu, and implementation